Social Support and Success of Career Woman (A Case Study on Female Staffs of Islamic Banks in Malang) - Utaminingsih, Alifiulahtin; Maskan, Mohammad (Institute of Research and Community Service, University of Brawijaya, 2017)
The purpose of the study is to analyze on structural dimension model of social support towards success of career female staffs of Islamic Banks in Malang, using management of conflict between work and family towards job satisfaction, commitment and performance. It is an explanatory research or hypothesis-testing study with descriptive quantitative approach. The subjects are 146 married female staffs; they have been working for the banks and married for at least one year. The sampling method is the multistage sampling method. The data collection method is questionnaire as the main instrument and supported by observation and documentation. The data analysis method is SEM (GeSCA) with the five-point Likert scale. The percentage of the contribution of social support, work conflict and commitment to organization to describe various degree of working performance is 78.5%. High social support and commitment to organization result in an increase in working performance of the Islamic bank female staffs.Keywords: Social support, career woman and Islamic Bank